ANALYZING COHESION AND COHERENCE IN SENIOR HIGH SCHOOL STUDENTS' EXPOSITORY ESSAYS: DISCOURSE FEATURES AND PEDAGOGICAL IMPLICATIONS - Kristina Gita Permatasari; Munawar Munawar (SENSEI RESEARCH CENTER, 2025)
Writing an expository essay is not easy for the students because they must arrange their ideas well so that the reader can understand. Two important things in writing are cohesion and coherence. This study discusses the analysis of cohesion and coherence in students' expository essays. The study used a qualitative descriptive method with discourse analysis. The data were the essays written by the students. The essays were analyzed based on the cohesive devices and also the coherence. The result shows that the students use many conjunctions but sometimes they are not appropriate, and the coherence of the essays is still weak especially in the relation between the thesis and the supporting paragraphs. It is suggested that the teachers teach cohesion and coherence explicitly.